A common TBP-binding site mutation elevates fetal hemoglobin levels by competitive globin switching change in β-thalassemia - Mengyang Song; Xiaolei Wei; Hualei Luo; Jueheng Wang; Yuhua Ye; Lang Qin; Chao Niu; Yong Long; Xingmin Wang; Congwen Shao; Miao Yu; Feng Gu; et al. (Blood Advances, 2025)
Abstract: β-Thalassemia is a common monogenic disorder caused by genetic defects in β-globin genes (HBB) resulting in imbalanced synthesis of α-/β-globin and ineffective erythropoiesis. It has been well documented that patients with β-thalassemia, or even carriers, mostly experience reactivation of fetal hemoglobin (Hb F), but its underlying mechanisms are incompletely understood. We took advantage of a previously established cohort of 1142 patients with β-thalassemia with diverse thalassemic mutations subjected to targeted next-generation sequencing. Genotype-phenotype association studies demonstrated that the HBB:c.-78A>G had a remarkable effect on the elevation of Hb F levels compared with other β-thalassemic mutations. To experimentally validate this conclusion, the ribonucleoprotein transfection complex through homology-directed repair by electroporation was performed, from which we observed a consistent increase of Hb F expression in both HUDEP-2 and primary CD34+ cell lines. Furthermore, chromatin immunoprecipitation–quantitative polymerase chain reaction, dual-luciferase reporter assay, and circular chromosome conformation capture (4C) assays validated a decreased occupancy of the HBB TATA box by TATA-binding protein (TBP), leading to boosted expression of γ-globin genes by enhanced interaction between locus control regions (LCRs) and γ-globin gene promoters. The patient-based investigation and experimental validations presented in this study might lead to a better understanding of stage-specific globin-gene expression mediated by competitive binding of distal enhancers (LCRs).